2018
DOI: 10.1016/j.athoracsur.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Right Axillary Mini-Thoracotomy for Correction of Ventricular Septal Defects and Complete Atrioventricular Septal Defects

Abstract: Background. Vertical right axillary mini-thoracotomy (VRAMT) is the standard approach for correction of atrial septal defect and partial atrioventricular septal defect at our institution. This observational single-center study compares our initial results with the VRAMT approach for the repair of ventricular septal defect (VSD) and complete atrioventricular septal defect (CAVSD) in infants and children to an approach using standard median sternotomy (MS). Methods. The perioperative courses of patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
(40 reference statements)
0
20
0
3
Order By: Relevance
“…Younger age is not a contraindication as it is possible even in infants. 4,5,10 Heinisch et al have demonstrated use of this approach for successful closure of ventricular septal defects and complete atrioventricular septal defects in 25 patients aged 4.3 months (3.3-6.3) with median weight of 5 kg (4.4-6.2) with results comparable to the median sternotomy approach. 10 A 4- to 5-cm incision gives adequate exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Younger age is not a contraindication as it is possible even in infants. 4,5,10 Heinisch et al have demonstrated use of this approach for successful closure of ventricular septal defects and complete atrioventricular septal defects in 25 patients aged 4.3 months (3.3-6.3) with median weight of 5 kg (4.4-6.2) with results comparable to the median sternotomy approach. 10 A 4- to 5-cm incision gives adequate exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al ( 10 ) performed VSD closure right vertical infraaxillary thoracotomy (RVIAT) in 274 patients, and they commented that the RVIAT can be performed with favorable cosmetic and clinical results for VSD closure. Similarly, Heinisch et al ( 14 ) performed VSD and complete AVSD correction in 84 patients with vertical right axillary mini-thoracotomy ( n = 25) and median sternotomy ( n = 59). No significant differences were observed for aortic cross-clamp duration, intensive care unit stay, hospital stay, and echocardiographic follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…13 More recently, however, a vertical skin incision at the midaxillary line has been proposed and results described in large series. 14 Proponents of this approach, while enthusiastic about the cosmetic result, admit that central cannulation is more challenging compared to the anterior minithoracotomy as the aorta and both cavae are farther away with the transaxillary approach. Thus, most recommend familiarity with the submammary incision before taking on the transaxillary approach.…”
Section: Transaxillary Approachesmentioning
confidence: 99%